THE MAPPING OF READING STRATEGIES BY THE STUDENTS OF SMP N 3 PLERET - Dewi Nur Widiyati (Universitas Sarjanawiyata Tamansiswa, 2019)
The aims of the study are to find out whether the students have certain reading strategies in comprehending English texts and what reading strategies are applied by students in comprehending English texts. The research is an ex-post facto study. The subjects were 88 students of class VIIA, VIIB, and VIID. The sample was random sampling method. The data collection method was surveying by filling out the questionnaire. The items in the research instrument were developed by adopting reading strategies by Thomas Kral (1995). Questionnaire items were developed in nine items and divided into four types of strategies: surveying, scanning, skimming, and phase reading. The data analysis was based on descriptive statistics obtained from the results of data processing through quantitative descriptive. The results indicate that students of class VII A, VIIB, and VIID of SMP N 3 Pleret usually used a reading strategy of surveying (mean 4.06) and phase reading (mean 4.0). When they read English texts, they already have awareness to find out what reading strategies they have to apply so that they are able to comprehend the texts. The mean values of scanning and skimming strategies are 3.56 and 3.19. The strategies were sometimes applied by students in comprehending English texts.